Perils of Empire - Jay Willoughby (American Journal of Islam and Society, 2008)
TheAssociation ofMuslim Social Scientists of NorthAmerica (AMSS) held its 36th annual conference at the University ofMaryland from26-28 October 2007. Co-sponsored by the university’s Department of Government and Politics and featuring Dr. Charles E. Butterworth as its program chair, the presenters discussed the “Perils of Empire: Islamophobia, Religious Extremism, and the New Imperialism.” In his opening remarks, Butterworth mentioned that he had been “somewhat taken aback” buy the theme, but that after five months he found that the “topic is most just.” ...